The Effect of TPACK-Based Learning Using Avenza Maps on Student Learning Activities in Mapping Materials - Dian Ayu Pratiwi; Rahma Hayati; Juhadi Juhadi; Apik Budi Santoso; Erni Suharini (JURNAL GEOGRAFI, 2026)
While studying geography, students work to develop a theoretical grasp of the subject as well as practical skills in spatial reasoning and analysis through hands-on experience with real-world phenomena. There has been little use of GIS technology in Indonesian geography classes, despite its widespread accessibility. This research examines the deployment of TPACK-based learning in mapping materials using the Avenza Maps program and its influence on student learning activities. Proposive sampling was used to choose XE-7 pupils from Senior High School 13 Semarang as part of the descriptive quantitative methodology. We used descriptive and inferential statistics to examine the link and its effects based on data gathered through structured observation, surveys, and documentation. The findings show that, overall, students' learning activities, instructors' TPACK-based techniques, and the use of Avenza Maps are all excellent. Specifically in the areas of visual, motor, and emotional processing, as well as oral skills that need reinforcement, students' engagement levels rose from 73.33% to 75% between the first and second sessions, according to observations. Strong positive correlations among TPACK competency, Avenza Maps use, and student engagement are shown by Pearson correlation (r=0.894, 0.888, 0.771; p<0.01). Multiple regression also demonstrates that TPACK and Avenza Maps have substantial beneficial impacts. These factors account for 89.7 percent of the variation in student activity, as indicated by the coefficient of determination (R2 = 0.897). The results of this research show that a smart way to encourage active, practical, and student-centered geography learning is for instructors to combine their TPACK expertise with effective use of geospatial technology.